Perbaikan Kualitas Pembatikan pada CNC Batik Tulis Rotary Bed Menggunakan Metode Taguchi - Hamidi, Kurniawan; Wibisono, Muh. Arif (Journal of Digital Ecosystem for Natural Sustainability, 2023)
The nglowongi process is one part of the batik process, which is making patterns on mori. As technology develops, this process is replaced by machines that apply CNC technology, namely the CNC rotary bed. In its implementation, obstacles were found such as failure to form motifs that have perfect angles on the fabric. There are many possible factors that cause the failure, but the authors focus on the limiting factors on the speed and acceleration of the stepper motor movement and the design angle of the motif. The purpose of this research is to optimize the input setup (speed and acceleration) on GRBL during the process of making angular motifs on batik cloth. The method used is the Taguchi method and two way-ANOVA. The results of this study indicate that the optimal combination of motif design angle, speed and acceleration is 91°-180°, 833.33 mm/s or 500 mm/min respectively and the input acceleration is 4000 mm/s2